Improvement of semi-resolved CFD-DEM model for seepage-induced fine-particle migration: Eliminate limitation on mesh refinement. (June 2019) - Yang, Qing; Cheng, Kuang; Wang, Yin; Ahmad, Mahmood
Abstract: The semi-resolved CFD-DEM model, proposed in our previous paper (Cheng et al., 2018) for the modelling of seepage-induced fine-particle migration through coarse skeleton in gap-graded soils, is improved through using Gaussian-based weighting function for fine particle-fluid coupling based on locally averaging theory. By doing so, it eliminates the limitation on fine particle-fluid mesh size ratio and thereby facilitates capturing detailed flow pattern through the coarse skeleton by refining fluid meshes. The improved semi-resolved CFD-DEM model is validated by Particle Image Velocimetry results of velocity field of fine glass beads migration through a simple coarse skeleton.